Latin American and Caribbean research on nutrition: Analysis of the period 2000-2023 in Scopus - Cadenas, Gladis Jane Villanueva; Crispin, Norma Elvira Muguruza; Agama, Elizabeth Judith Pablo; Lazaro, Cesar Eloy Gamarra; Quinteros, Carmen Del Pilar Alvarez (Iberoamerican Journal of Science Measurement and Communication (Online), 2025)
Objective. This study aims to examine Latin American and Caribbean scientific production in nutrition, specifically its presence in the Scopus database from 2000 to 2023. Design/Methodology/Approach. A bibliometric methodology was implemented to identify the main research areas by analyzing social networks and reviewing the literature. In this sense, the distinctive characteristics of the articles published on nutrition in the Latin American and Caribbean regions were examined in Scopus. Results/Discussion. There is evidence of a wide range of authorship and the formation of various clusters, predominantly in countries such as Brazil, Mexico, and the United States. There is limited thematic specialization and a significant presence of transient authors. The articles published in 2017 and 2019 have had the most significant impact on nutrition research. Conclusions. There is evidence of stability in the growth of scientific output on nutrition. Brazil's leadership stands out in the analysis, corresponding with the higher periods reported in the country indexes according to the Scimago Journal Rank. Originalidad/Valor. Although it is not common to find bibliometric studies exclusively focused on this subject, various literature reviews have been carried out, either as a type of independent study or as part of the analysis of the resulting research.